Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.